Temporal and financial analysis of hospitalizations for pneumonia in the brazilian childhood population (Research, Society and Development, 2024)
Objective: To identify the epidemiological characteristics of children and adolescents hospitalized due to pneumonia, as well as to describe the public costs allocated to this purpose over the last decade in Brazil. Methodology: Descriptive and retrospective ecological study carried out in January 2024, using the Hospital Information System (SIH/SUS). Annual data on hospital service prices and average length of stay for children and adolescents affected by pneumonia from 2013 to 2022 were included, in addition to analysis of the number of hospitalizations according to sex, age group up to 19 years old and Brazilian regions. Result: In the period between 2013 and 2022, it was observed that 52.5% of the budget allocated to treatment for hospitalizations for diseases of the respiratory system was directed only to pneumonia, with spending peaking in 2022. In relation to the year, 2013 presented more cases of hospitalizations for pneumonia (311,364 cases), with the analysis of the average length of hospital stay there was consistency, a total average of 5.2 days in the years analyzed. The sociodemographic profile revealed a higher frequency of cases in the Southeast region (33%), in males (54.37%) and in the age group of 1-4 years (46.52%). Conclusion: Based on this study, it was possible to infer that the growth in the number of hospitalizations for pneumonia in the Brazilian child and youth population is directly proportional to the hospital expenses analyzed in the last decade, leading to the need for public policies for prevention and health promotion, in addition to preservation environment and the promotion of education and infrastructure.